Spatial Localization of Sources in the Rat Subthalamic Motor Region Using an Inverse Current Source Density Method - van Dijk, Kees J.; Janssen, Marcus L. F.; Zwartjes, Daphne G. M.; Temel, Yasin; Visser-Vandewalle, Veerle; Veltink, Peter H.; Benazzouz, Abdelhamid; Heida, Tjitske (Frontiers in Neural Circuits, 2016)
Objective: In this study we introduce the use of the current source density (CSD) method as a way to visualize the spatial behavior of evoked responses in the rat subthalamic nucleus (STN) at fixed time stamps resulting from motor cortex stimulation. This method offers opportunities to visualize neuronal input and study the relation between the synaptic input and the neural output of neural populations. Approach: Motor cortex evoked local field potentials and unit activity were measured in the subthalamic region, with a 3D measurement grid consisting of 320 measurement points and high spatial resolution. This allowed us to visualize the evoked synaptic input by estimating the current source density (CSD) from the measured local field potentials, using the inverse CSD method. At the same time, the neuronal output of the cells within the grid is assessed by calculating post stimulus time histograms. Main results: The CSD method resulted in clear and distinguishable sources and sinks of the neuronal input activity in the STN after motor cortex stimulation. We showed that the center of the synaptic input of the STN from the motor cortex is located dorsal to the input from globus pallidus. Furthermore, our results indicate that the long-latency, long-duration inhibitory period following motor cortex stimulation is caused by activation of inhibitory synapses. Significance: For the first time we have performed CSD analysis on motor cortex stimulation evoked LFP responses in the rat STN as a proof of principle. Our results suggest that the CSD method can be used to gain new insights in the spatial extent of synaptic pathways in brain structures and neural circuits.